Measurements of Poverty in Indonesia : 1996, 1999, and Beyond - Pradhan, Menno; Suryahadi, Asep; Sumarto, Sudarno; Pritchett, Lant (World Bank, Washington, DC, 2015)
Indonesia's economic crisis has caused a consumption expenditures deterioration in the welfare of Indonesians. Focusing on only one dimension of individual, and family welfare - consumption expenditures - the authors analyze two issues associated with the measurement of poverty. The first issue is how to produce regionally consistent poverty lines - that is, how to define a level of spending for each region that produces the same material standard of living. Without comparable data on prices, there is a problem of circularity. Choosing the reference population is important for defining the price level by which to deflate money expenditures to reach the same welfare level, but one needs to know the price level to define the reference population as a group with the same real expenditures. To address the problem of circularity, the authors use an iterative approach to defining poverty, one that produces consistent results across regions. They then use those poverty lines to examine the common "poverty profiles" (by location, sector, and so on). The second issue is more conceptual: how to expand the narrow measure of poverty, based on spending for consumption, with extensions that expand how welfare is measured, and allow more consistent comparisons of different individuals' welfare levels.